A comparative study of adhesion of melanoma and breast cancer cells to blood and lymphatic endothelium - Safuan, Sabreena; Storr, Sarah J.; Patel, Poulam M.; Martin, Stewart G. (Mary Ann Liebert, 2012)
Background: Lymphovascular invasion (LVI) is an important step in the metastatic cascade; tumor cell migration and adhesion to blood and lymphatic vessels is followed by invasion through the vessel wall and subsequent systemic spread. Although primary breast cancers and melanomas have rich blood vascular networks, LVI is predominately lymphatic in nature. Whilst the adhesion of tumor cells to blood endothelium has been extensively investigated, there is a paucity of information on tumor cell adhesion to lymphatic endothelium. Methods and Results: Breast cancer (MDA-MB-231 and MCF7) and melanoma (MeWo and SKMEL-30) cell adhesion to lymphatic (hTERT-LEC and HMVEC dLy Neo) and blood (HUVEC and hMEC-1) endothelial cells were assessed using static adhesion assays. The effect of inflammatory conditions, tumor necrosis factor-a (TNF-a) stimulation of endothelial and tumor cells, on the adhesive process was also examined. In addition, the effects of TNF-a stimulation on tumor cell migration was investigated using haplotaxis (scratch wound) assays. Breast cancer and melanoma cells exhibited higher levels of adhesion to blood compared to lymphatic endothelial cells ( p < 0.001). TNF-a stimulation of endothelial cells, or of tumor cells alone, did not significantly alter tumor–endothelial cell adhesion or patterns.When both tumor and endothelial cells were stimulated with TNF-a, a significant increase in adhesion was observed ( p < 0.01), which was notably higher in the lymphatic cell models ( p < 0.001). TNF-a-stimulation of all tumor cell lines significantly increased their migration rate ( p < 0.01). Conclusions: Results suggest that metastasis resultant from lymphatic vessel-tumor cell adhesion may be modulated by cytokine stimulation, which could represent an important therapeutic target in breast cancer and melanoma.